The clinical significance of posttraumatic malunions of lower extremities long bones - Romanenko, Kostiantyn; Doluda, Yaroslav; Prozorovskiy, Dmytro; Pariy, Vasyl (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The treatment of patients with long bones fractures, despite the development and improvement of treatment methods and fixing devices in certain cases can lead to unwanted results such as a formation of posttraumatic deformity — malunion. Objrctive. To provide modern approach regarding clinical significance and necessity of correction of secondary changes in moving segment that appeared as a result of formation of lower extremity malunion. Methods. The results of treatment of 196 patients were analyzed (89 men, 107 women; age from 19 to 76 years). All the patients had the malunion of the long bones of lower extremities and have been treated from 2004 to 2019 years. Analysis of special literature and own experience was performed to identify the effects of malunions. Results. It was shown that formed malunion lead to tangible shortening of injured extremity, joints overloading and muscle function violation. Malunions are compensated by the means of changing in movement arch and gait pattern. While it is noted that unphysiological load on joints, that predispose the development of degenerative changes, and muscle fatigue and pain are the results of muscle work to support inadequate position of the joints. Malunions on the level of femur and tibia became clinically significant on condition of severe restriction of extremity function, thus its restoration is the goal of treatment. Different cases of malunion development were considered: varus, valgus, antecurvatio, recurvatio, translation, torsion malalignment. Clinical examples are given. Conclusions. Clinical significance of different malunions depend upon their localization, presence and severity of secondary changes, status of injured extremity and physical condition of the patient, his or her individual demands. Secondary changes can play the role of compensation and spread on injured extremity, sacro-iliac joints, lumbar spine, contralateral extremity. The assessment of secondary changes of musculoskeletal system is mandatory for the patients with malunions during the planning of treatments measures. The indication for surgical correction should be defined with taking into consideration possible development of malunion complications in future.